ANALISIS HUBUNGAN AKTIVITAS FISIK DENGAN INDEKS MASSA TUBUH (IMT) PADA MAHASISWA PROGRAM STUDI OLAHRAGA DAN KESEHATAN - Haris Ardiansyah; Muhammad Nur Ikhsan; Hendra; Andri Ardianto; Mohd Adrizal; Ely Yuliawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the relationship between physical activity and Body Mass Index (BMI) among students of the Sports and Health Study Program. This research employed a quantitative method with a correlational approach. The sample consisted of 31 students selected using purposive sampling techniques. Physical activity data were obtained through the International Physical Activity Questionnaire (IPAQ) Short Form distributed online, while BMI data were calculated based on the respondents' height and weight. Data were analyzed using descriptive statistics and Spearman Rank correlation analysis because the data were not normally distributed. The results showed that the mean score of physical activity was 72.03, while the mean BMI was 21.61. The Spearman correlation test revealed a correlation coefficient of 0.171 with a significance value of 0.356 (p > 0.05). These findings indicate that there is no significant relationship between physical activity and Body Mass Index (BMI) among students of the Sports and Health Study Program. The relationship between the two variables was categorized as very weak and positive. Therefore, physical activity is not the only factor affecting BMI, as other factors such as dietary patterns, age, sex, genetic factors, sleep quality, and lifestyle also contribute to an individual's nutritional status.